Detection of replication-competent and pseudotyped human immunodeficiency virus with a sensitive cell line on the basis of activation of an integrated beta-galactosidase gene. - Kimpton, J (1992)
We have constructed a HeLa cell line that both expresses high levels of CD4 and contains a single integrated copy of a beta-galactosidase gene that is under the control of a truncated human immunodeficiency virus type 1 (HIV-1) long terminal repeat (LTR). This cell line, called CD4-LTR/beta-gal, can be used to determine quantitatively the titer of laboratory-adapted HIV strains, and the method used to do so is as sensitive as the determination of viral titers in a T-cell line by end point dilution. Using this cell line as a titer system, we calculated that HIV-1 stocks contain only one infectious particle per 3,500 to 12,000 virions. Virus derived from a molecular clone of a macrophagetropic provirus will not infect this cell line. We have also cocultivated peripheral blood lymphocyte cultures from HIV-infected individuals with the CD4-LTR/beta-gal indicator cells. In a majority of primary isolates (five of eight), including isolates from asymptomatic patients, rare virus-infected cells that can activate the beta-galactosidase gene are present.